Innovation system: a structural study for Poland - Wojewnik-Filipkowska, Anna; Szczepaniak, Krzysztof; Zamojska, Anna (System innowacji: ujęcie strukturalne dla Polski, 2019)
Most countries implement a policy supporting the commercialization of research. There are several institutionalized forms and initiatives supporting research, development and innovation (RDI) transfer between university and business. The research is driven by the question of Polish RDI institutions’ efficiency and effectiveness, while more generally it aims to contribute to a theoretical understanding of the innovation system. The article builds on the economic studies of the National Innovation System (NIS) and Triple Helix Concept, highlighting the need for a structural style study. This is used to create a NIS case study for Poland, and provides an audit of systemic features and issues based on qualitative information, using a particular framework respecting three levels of stakeholders and investment viewpoints. The research has a descriptive but also a normative character
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 117-129
Keywords: NIS; triple helix; research and development infrastructure; evaluation; NSI; potrójna helisa; model potrójnej spirali; infrastruktura badawczo-rozwojowa; ewaluacja